The Transformation of the Economy: Exploring the Impacts and Opportunities of the Digital Economy - Omar Al-Kasasbeh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The digital revolution has brought about significant changes to the global economy, creating a new paradigm known as the digital economy. This article delves into the various aspects of the digital economy, examining its impacts and exploring the opportunities it presents for businesses, industries, and society as a whole. The study investigates the key drivers and characteristics of the digital economy, such as digital platforms, data-driven innovation, and technological advancements. It analyzes the transformative effects of the digital economy on traditional sectors and highlights the potential for enhanced productivity, innovation, and economic growth. Additionally, the article examines the challenges and policy considerations in harnessing the full potential of the digital economy, including issues related to the digital divide, data privacy, and cybersecurity. By understanding the dynamics of the digital economy, policymakers, businesses, and individuals can adapt and leverage digital transformation for sustainable economic development and inclusive growth.